Impact of manufacturing variables on the mechanical performance of recycled glass-enhanced composites - Nathaphon Buddhacosa; Thevega Thevakumar; Everson Kandare; Sujeeva Setunge; Dilan Robert (Cleaner Materials)
This study investigated the influence of various manufacturing conditions – including moulding pressure, post-curing, and aging – on the microstructure and mechanical properties (flexural and tensile) of epoxy matrix composites incorporating recovered glass particles at weight fractions ranging from 84 wt% to 90 wt%. The study focused on understanding how these conditions affect the interfacial bonding between the glass particles, epoxy matrix, and void content to establish a correlation between microstructure and mechanical performance before and after ceramification. The findings revealed that increasing moulding pressure from 1.1 MPa to 6.6 MPa reduced void content, increased composite density, and significantly improved flexural properties. The impact of post-curing on the composites’ flexural performance was also examined, and it was found that adjusting the epoxy matrix weight fraction from 6 wt% to 12 wt% further influenced the composite’s mechanical properties. X-ray computed tomography (CT) and scanning electron microscopy (SEM) analyses revealed changes in composite porosity and interfacial bonding, enabling the correlation of these microstructural changes with variations in mechanical properties for both non-ceramified and ceramified composites. Ceramification induced additional microstructural changes, including the formation of voids, which influenced the composites’ mechanical properties. Additionally, the effect of integrating steel wire mesh with 6.5 mm apertures on the mechanical performance of the glass/epoxy composites, both before and after ceramification, was explored.